Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jth.12999
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation management during multivessel coronary artery bypass grafting: a randomized trial comparing individualized heparin management and conventional hemostasis management

Abstract: To cite this article: Hoenicka M, Rupp P, M€ uller-Eising K, Deininger S, Kunert A, Liebold A, Gorki H. Anticoagulation management during multivessel coronary artery bypass grafting: a randomized trial comparing individualized heparin management and conventional hemostasis management. J Thromb Haemost 2015; 13:1196-206.Summary. Background: Individualized heparin management (IHM) uses heparin dose-response curves to improve hemostasis management during cardiac surgery as compared with activated clotting time-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…164 A more recent study investigated how Hepcon-based heparin and protamine management influenced heparin and protamine doses compared to a conservative anticoagulation strategy in patients having CABG surgery. 165 The study showed no differences in total heparin doses between groups, but protamine dosing was significantly reduced in the Hepcon group. This reduction was associated with an increase of 75 ml in the 12-h blood loss but not with differences in transfusion requirements.…”
Section: Interventionsmentioning
confidence: 82%
“…164 A more recent study investigated how Hepcon-based heparin and protamine management influenced heparin and protamine doses compared to a conservative anticoagulation strategy in patients having CABG surgery. 165 The study showed no differences in total heparin doses between groups, but protamine dosing was significantly reduced in the Hepcon group. This reduction was associated with an increase of 75 ml in the 12-h blood loss but not with differences in transfusion requirements.…”
Section: Interventionsmentioning
confidence: 82%
“…150,151,153,[158][159][160] In contrast, others did not show favourable results for blood loss and transfusion requirements when heparin titration was compared with an ACT-based protocol. 152,[161][162][163] Due to the lack of perioperative bleeding and transfusion rates as primary end points in these studies, larger multicentre RCTs are required to determine the added value of individual heparin management. Alternative methods of heparin management and anticoagulation monitoring during ECC consist of the determination of anti-factor Xa activity.…”
Section: Description Of the Evidencementioning
confidence: 99%
“…A recent RCT in patients having CABG showed that a protamine-to-heparin dosing ratio o0.6 was associated with significantly more blood loss within 12 h after surgery [420 ml (interquartile range 337-605 ml) vs 345 ml (interquartile range 230-482 ml); P ¼ 0.0041], but no difference in PRBC transfusion was noted (2.3 units vs 2.7 units; P ¼ 0.83) compared to patients subjected to a ratio 40.8. 152 Ideally, protamine should be administered in a dose that matches actual heparin levels after the termination of ECC. It is advised not to exceed a protamine dose in a 1:1 ratio to the initial heparin bolus, because protamine overdosing might be associated with perioperative bleeding and enhanced transfusion requirements.…”
Section: Protaminementioning
confidence: 99%
“…Further details have been published elsewhere. 7 All but one patient were operated by the same staff surgeon. CECC and MECC patients received intermittent antegrade warm blood cardioplegia 8 during aortic crossclamp time.…”
Section: Surgical Detailsmentioning
confidence: 99%
“…The prospective randomized HEPCON trial 7 investigated the influence of individualized versus conventional heparin management and of surgical technique, that is, conventional extracorporeal circulation (CECC), minimized extracorporeal circulation (MECC), and off-pump coronary artery bypass grafting (OPCAB) on heparin and protamine doses in patients treated for multivessel coronary artery disease. The present manuscript focuses on the effects of surgical technique on perioperative kidney function, as well as on kidney injury within 72 hours after surgery, as a secondary endpoint of this study.…”
Section: Introductionmentioning
confidence: 99%